Characterization of casting defects in a Fe-rich Al-Si-Cu alloy by microtomography and finite element analysis. (1st October 2017) - Bacaicoa, I.; Wicke, M.; Luetje, M.; Zeismann, F.; Brueckner-Foit, A.; Geisert, A.; Fehlbier, M.
Highlights: The data obtained from micro computed tomography were imported into a FE Software tool. The stress concentration factors caused by the shrinkage pores and the ß-Al5 FeSi inclusions were calculated. Agglomerations of ß-Al5 FeSi inclusions in large clusters were observed. After heat treatment, the ß-Al5 FeSi inclusions dissolve and ductility increases. Abstract: The casting defects from a Fe-rich Al-Si-Cu alloy were characterized by micro tomography and Finite Element Analysis. The specimens were analyzed in a high resolution computed-tomography scan and the 3D geometry of the casting defects were segmented in a rendering software. Shrinkage pores of various shapes as well as large plate-like ß-Al5 FeSi inclusions were identified and their 3D volumetric model was imported into a FE software tool in order to calculate the stress concentration factors caused by these defects. In the case of the shrinkage pores, maximum Kt factors ranging from 4.73 and 14.56 were obtained located at the holes and dendritic arms of the shrinkage pores. For the ß-Al5 FeSi particles, the highest stress concentration factors were located at the edge and the protuberances of the inclusions and ranged between 1.74 and 3.46. Large clusters of these ß-phases were observed, in which micro-pores were retained. After heat treatment, a significant fragmentation and dissolution of the ß-Al5 FeSi inclusions was found together with an increase in the ductility and ultimate strength of the alloy.